Effects of urban pollution on zooplankton diversity along the Almada River (Bahia, Brazil) - Jovenilson Ferreira dos Santos; Jaielle Rodrigues Nascimento; Nadson Ressyé Simões (Acta Limnologica Brasiliensia)
Abstract: Aim This study aimed to analyze the influence of small cities on the diversity of the zooplankton community along the Almada River, Bahia. Methods The samples were collected at points upstream (Clean Waters - CW) and downstream (Active Decomposition - DA) of the urban area of three cities: Almadina, Coaraci and Itajuípe, between the years 2020 and 2023. Results Among the physical and chemical variables, only dissolved oxygen and water temperature varied significantly between CW and DA. 90 taxa were identified, of which: 60 from Rotifera, 17 from Cladocera and 13 from Copepoda. It was possible to verify the presence of dominant taxa, characteristic of eutrophic environments, in points downstream of urban areas, namely: Lecane bulla bulla, Bdelloidea, Testudinella patina and Platyias quadricornis. The community attributes with significant variation between CW and DA were: abundance, evenness and the Shannon diversity index. The Jaccard dissimilarity between the CW and DA zones was high, indicating a low rate of species sharing between the CW and DA zones. In the BIOENV analysis, the variables of dissolved oxygen and electrical conductivity associated with variation in community structure were chosen. Conclusions pollution from urbanized regions in the Almada River reduces the evenness and diversity index of shannon, and increases the abundance of the zooplankton community.